Cruris Cellulitis in an Elderly Man with Multiple Comorbidities and Lifestyle Risk Factors - Kuntadi Syamsul Hidayat, Muhammad; Eryadi, Usep; Aadillah Hafidzoh Subagyo, Khonsaa (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Background: Cellulitis is a bacterial skin infection that can progress to serious complications, particularly in patients with multiple comorbidities. This case report discusses a 60-year-old male with cellulitis of the left cruris, accompanied by type 2 diabetes mellitus, hypertension, dyslipidemia, and obesity. Case Presentation: The patient presented with redness, swelling, warmth, and pain in the left lower limb, along with systemic symptoms such as fever and fatigue. His medical history revealed poorly controlled diabetes mellitus, hypertension, and dyslipidemia, exacerbated by obesity. Further assessment indicated inadequate health knowledge and unhealthy lifestyle habits, including poor dietary choices and a lack of physical activity. Laboratory findings showed elevated blood glucose levels, dyslipidemia, and markers of inflammation. The patient was treated with intravenous antibiotics, glycemic control therapy, antihypertensive medication, and supportive care. The role of the family is essential in supporting the success of long-term therapy. Discussion: Cellulitis in patients with multiple metabolic disorders poses a higher risk of complications, including recurrent infections, delayed wound healing, and sepsis. Poor health literacy and unhealthy lifestyle habits further contribute to disease progression. Comprehensive management involving antibiotic therapy, metabolic control, patient education, and lifestyle modifications is essential for improving clinical outcomes. Conclusion: This case highlights the importance of early diagnosis and a multidisciplinary approach to managing cellulitis in patients with multiple comorbidities. Addressing underlying risk factors, including inadequate health knowledge and unhealthy lifestyles, is crucial to preventing recurrence and complications.